PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN TRAVEL DI KABUPATEN MALAKA (Studi Pada Travel Betun Mandiri Expres) - Yuventus K K Finistyawan; Juita L D Bessie (Universitas Nusa Cendana, 2020)
This research aims to determine the effect of service quality on customer satisfaction of Betun Mandiri Express (BME) Car Travel. The independent variable in this study is the dimension of service quality consisting of physical evidence, reliability, responsiveness, assurance, and empathy, while the dependent variable is customer satisfaction. The number of samples is 99 respondents who ever using BME Car Travel services more than twice. Samples were gained using accidental sampling technique. Data were collected using questionnaires, interviews, observations, and literature studies. Data analysis techniques used are quantitative descriptive, multiple linear regression analysis and hypothesis testing using the Software SPSS 24. Descriptive Analysis's results show that overall, the respondents gave a categorized perception assessment both for the five dimensions of Service Quality and Satisfaction of using BME Travel. From the results of Multiple Linear Regression Analysis found the mathematical equation: Y = 2.537 + 0.174X1 + 0.158 X2 + 0.185 X3 + 0.146 X4 + 0.196 X5.Both the F Test and t Test results show that simultaneously and partially the five dimensions of Service Quality have a significant effect on customer satisfaction. However, based on the value of Adjusted R2 shows the contribution of the variable Service Quality to Customer Satisfaction is only 32.2%. While 67.8% is influenced by other variables outside the focus of this study. These variables are price and promotion which can be considered for further researchers besides service quality. Keywords: Tangibles, Reliability, Responsiveness, Assurance, and Empathy and Customer Satisfaction